Optimizing Traditional Games as Learning Media: A Literature Review on Cultural and Character Education - Deya Harpina; Musawer Hakimi (Balai Publikasi Indonesia, 2025)
Using basic, environment-appropriate equipment and the results of cultural research that have been passed down from generation to generation in an area, traditional games may amuse kids. In this instance, integrating traditional games into education may be a unique set of values in the preservation, comprehension, and upkeep of cultural values while educating youngsters and having an effect on their characteristics. To successfully and meaningfully include conventional games into a child's educational environment. This entails modifying and improving conventional games so that kids may utilize them as useful teaching aids. Therefore, the goal of this essay is to further study the theory around the optimization of classic games as learning tools. This research's data was gathered by employing the literature study research method from a variety of literature sources that are pertinent to the subject or research issue under consideration. A thorough review and synthesis of pertinent studies has also been done in this study's literature study. The findings demonstrate that we may make learning interesting, participatory, and relevant for kids by utilizing the possibilities of traditional games. Challenges that could appear include a centralized curriculum, a modern viewpoint that disregards traditional games, logistical and facility issues, as well as community acceptance and involvement. These obstacles may be addressed, though, through understanding, and cooperation between parents, educators, and the community, as well as initiatives to imaginatively incorporate traditional games into children's learning.